2010
DOI: 10.1002/joc.2238
|View full text |Cite
|
Sign up to set email alerts
|

Observed changes in extreme weather indices in Hong Kong

Abstract: Past trends of the occurrences of extreme temperature and rainfall events in Hong Kong from 1885 to 2008 were examined using a suite of 27 extreme indices adopted from the core indices developed by the Expert Team on Climate Change Detection, Monitoring and Indices (ETCCDMI) under the auspices of the World Meteorological Organization (WMO), with appropriate modification to suit the sub-tropical climate of Hong Kong. Results showed that the extreme daily maximum and minimum temperatures, annual numbers of very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 22 publications
6
39
0
Order By: Relevance
“…Generally speaking, TN90p and TX90p can be considered as 'hot indices' and TN10p and TX10p as 'cold indices.' Detailed definitions of the indices have been well documented in other publications (Wong et al 2010, Lee et al 2011 and are not repeated here.…”
Section: Extreme Temperature Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, TN90p and TX90p can be considered as 'hot indices' and TN10p and TX10p as 'cold indices.' Detailed definitions of the indices have been well documented in other publications (Wong et al 2010, Lee et al 2011 and are not repeated here.…”
Section: Extreme Temperature Indicesmentioning
confidence: 99%
“…Analysis of the annual mean temperature in the region has shown a longterm increasing trend under the effect of global warming and local urbanization (Lee et al 2006, Ginn et al 2010. For extreme temperature events, re cent studies revealed that the extreme daily minimum and maximum temperatures in Hong Kong exhibited statistically significant long-term rising trends from 1885−2008 (Wong et al 2010, Lee et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown changes in the frequency and intensity of climate extremes over the past century (Alexander et al 2006;Dos Santos et al 2010;Frei and Schär 2001;Frich et al 2002;Kiktev et al 2003;Moberg and Jones 2005;Sen Roy and Balling 2004;Vincent et al 2005;Aguilar et al 2005;New et al 2006;Wong et al 2010;Hirschi et al 2011). Zong and Chen (2000) illustrated how devastating a single extreme precipitation event can be for human societies.…”
Section: Introductionmentioning
confidence: 99%
“…As El Niño and La Niña conditions could have effect on the monthly and seasonal climate of Hong Kong against the ENSO-neutral situation from a statistical perspective (Lee and Cheng 2011), the latest status and forecast of the warming and cooling of surface waters over the central and eastern equatorial Pacific Ocean are also closely monitored and reported in the HKO website for public reference. Long-term variations of various meteorological elements and indices, such as temperature, rainfall, sea level, tropical cyclone frequency, and extreme weather events, are also conducted to assess the climate change in Hong Kong due to global warming and local urbanizations (Lee et al 2010b;Wong et al 2011;Chan et al 2012). …”
Section: (H) Climate Monitoringmentioning
confidence: 99%
“…(e.g., Lee et al 2010b;Wong et al 2011). Looking into the future, Hong Kong can expect even warmer weather, more variable rainfall, more frequent extreme weather, and a sea level that keeps rising (HKO 2017a).…”
Section: Introductionmentioning
confidence: 99%